Low serum iron levels and risk of cardiovascular disease in high risk elderly population: Nested caseecontrol study in the PREvenci on con DIeta MEDiterr anea (PREDIMED) trial - Gutiérrez-Bedmar, Mario; Olmedo, Pablo; Gil, Fernando; Ruiz-Canela, Miguel; Martínez González, Miguel Ángel; Salas-Salvadó, Jordi; Babio, Nancy; Fito, Montserrat; del Val, José L.; Corella, Dolores; Sorlí, José V.; Ros, Emilio; et al. (Elsevier, 2021)
Epidemiological data on iron status and cardiovascular disease (CVD) are still controversial. The aim of this study was to determine whether low serum iron (SI) levels are associated with an increased odds of first CVD event in a population at high cardiovascular risk. Methods: Case-control study design nested within the "PREvención con DIeta MEDiterránea" (PREDIMED) trial. A total of 207 participants diagnosed with CVD (myocardial infarction, stroke or cardiovascular death) during follow-up period (2003-2010) were matched by sex, age and intervention group to 436 controls by incidence density sampling. Median time between serum sample collection and subsequent CVD event occurrence was 0.94 years. Inductively coupled plasma mass spectrometry analysis was used to determine SI levels. In-person interviews, medical record reviews, and validated questionnaires were used to assess covariates. Multivariable-adjusted odds ratios (ORs) of CVD were calculated with conditional logistic regression. Results: Mean SI levels were higher in men than in women (1224.0 μg/L vs. 1093.8 μg/L; p < 0.001). Among women, but not in men, the mean SI concentration was lower in cases than in controls (1008.5 μg/L vs. 1132.9 μg/L; p = 0.030). There was a gradual decrease in the multivariable-adjusted ORs of CVD with increasing SI levels (highest vs. lowest quartile: OR = 0.55, 95% CI: 0.32-0.93; ptrend = 0.020). This inverse relationship was more pronounced among women (highest vs. lowest quartile: OR = 0.15, 95% CI: 0.03-0.69; ptrend = 0.011). Conclusions: The present findings are consistent with previously reported inverse associations between SI and CVD. SI levels as an independent marker of short-term cardiovascular risk may be useful for risk assessment in older populations.
Keywords: Corazón - Enfermedades; Cardiovascular disease; Older populations; PREDIMED; Prospective studies; Serum iron